If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 3x = 45 Solving 16 + 3x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 3x = 45 + -16 Combine like terms: 16 + -16 = 0 0 + 3x = 45 + -16 3x = 45 + -16 Combine like terms: 45 + -16 = 29 3x = 29 Divide each side by '3'. x = 9.666666667 Simplifying x = 9.666666667
| 24+24=46+6 | | -37-5x=2x+15 | | 24+24=46+2 | | 2x+3(1.5)=2772 | | 5(y-1)=6(y-5) | | 1/3x-6=4+2x | | 9+8x=93 | | 4=7v-8/8+v-6/4 | | 4b-6-12b-4= | | 2x+3y=2772 | | x-25=5+11x | | K=-5/2 | | 3y-(-4y+3)=-17 | | (x-2)/6=(x+3)/9 | | 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 |